Fate of Free Fat Grafts with or without Adipogenic Adjuncts to Enhance Graft Outcomes. Issue 4 (October 2018) - Tang, Howard H.; Han, Xiao-Lian; Debels, Heidi; Tan, Beryl; Palmer, Jason; Poon, Christopher; Abberton, Keren; Morrison, Wayne
Abstract : Background: Free fat grafting is popular, but it is still unclear how it works. Although focusing on graft survival seems an obvious direction for improving clinical results, the authors' research suggests that long-term volume retention is in part attributable to new fat regeneration. Measures to facilitate adipogenesis may therefore be equally important. Methods: To investigate the relative roles of survival and regeneration of fat grafts, the authors measured the fate of human lipoaspirate implanted into the scalps of immunodeficient mice, with and without stromal vascular fraction and a porcine extracellular matrix (Adipogel). Specifically, the authors were interested in volume retention, and the composition of implanted or regenerated tissue at 6 and 12 weeks. Results: Free fat grafts exhibited poor volume retention and survival. Almost all of the injected human adipocytes died, but new mouse fat formed peripheral to the encapsulated fat graft. Adipogel and stromal vascular fraction improved proliferation of murine fat and human vasculature. Human CD34 + stromal cells were present but only in the periphery, and there was no evidence that these cells differentiated into adipocytes. Conclusions: In the authors' model, most of the implanted tissue died, but unresorbed dead fat accounted substantially for the long-term, reduced volume. A layer of host-derived, regenerated adipose tissue was present at the periphery. This regeneration may be driven by the presence of dying fat, and it was enhanced by addition of the authors' adipogenic adjuncts. Future research should perhaps focus not only on improving graft survival but also on enhancing the adipogenic environment conducive to fat regeneration.